Aplicación del Paradigma Ecológico Contextual y su relación con el aprendizaje de Geometría plana: en la unidad de triángulos, en el tercer semestre de la Escuela de Ciencias, Carrera de Ciencias Exactas, durante el período septiembre 2013-octubre 2014 - Rondal Urquizo, Celia Rosario (2016)
Plane geometry studies the properties and measurements of plane figures, the difficulty of learning lies in moving from working with concrete material to the ability of abstraction for building relationships and generalizations, by logical mental reasoning. This paper presents an alternative for learning Triangles; considering the Paradigm Ecological Context-conceiving teaching and learning as an interactive process, and a model of cultural learning, sharing and mediated; in which the teacher is a guide, technical, critical that enhances these interactions in a climate of trust, developing student abilities, skills, values and attitudes. The tutorial, based on this paradigm, "Plane Geometry Triangles" with clear objectives and orientations, is a useful instrument to facilitate the development of peer interactions, directing them to build their learning, capable of performing different shows being critical, reflective and applying their capacity for abstraction. We worked with the 11 students of the third semester of the school of Exact Sciences; the investigation was correlational and slitting, the design is field and quasi-experimental and to gather information a test and a survey were used. The study of triangles with the use of the didactic guide improved the relations between student-student and student-teacher; through collaborative interactive work, interspersed questions, examples for analysis and proposed exercises. After having a final grade, higher than the initial; it is concluded that the application of this paradigm with its model of interactive teaching and learning; the student becomes a whole being able to unwrap in the social environment.